A nonlinear model for the long-term hydro-thermal generation scheduling problem over multiple areas with transmission constraints - Martins, Leonardo S. A.; Soares, Secundino; Azevedo, Anibal T. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2009)
This paper presents a nonlinear model with individual representation of plants for the centralized long-term hydrothermal scheduling problem over multiple areas. In addition to common aspects of long-term scheduling, this model takes transmission constraints into account. The ability to optimize hydropower exchange among multiple areas is important because it enables further minimization of complementary thermal generation costs. Also, by considering transmission constraints for long-term scheduling, a more precise coupling with shorter horizon schedules can be expected. This is an important characteristic from both operational and economic viewpoints. The proposed model is solved by a sequential quadratic programming approach in the form of a prototype system for different case studies. An analysis of the benefits provided by the model is also presented. ©2009 IEEE.
Keywords: Hydro-thermal power systems; Long-term scheduling; Nonlinear optimization; Power transmission; Hydrothermal scheduling problems; Multiple areas; Non-linear model; Prototype system; Sequential quadratic programming; Thermal generation; Transmission constraint; Electric power transmission networks; Optimization; Quadratic programming; Scheduling